Application of 21st Century Learning Skills Oriented Digital-Age Literacy to Improve Student Literacy HOTS in Science Learning in Class IX SMP - Freddy Tua Musa Panggabean; Puspa Olivia Pardede; Rizky Mauli Dini Sitorus; Yani Kartini Situmorang; Evan S Naibaho; Juan Samuel Simanjuntak (Institute of Computer Science (IOCS), 2021)
The development of modernization and globalization of the 21st century has had a tremendous impact, one of which is the low thinking skills of students. This study aims to design and apply the PjBL model as one of the 21st century learning skills that is oriented towards digital-age literacy to improve student literacy HOTS in science learning on static electricity in class IX SMP. This research is a collaborative research study using descriptive qualitative research design classroom research.This research is a quasi-experimental research using a one group pretest-posttest design. The PjBL model oriented to digital-age literacy is designed according to the characteristics of 21st century skills learning known as 4C skills (creativity, critical thinking, communication, and collaboration). Learning is designed with digital teaching materials (e-modules) designed using theapplication Kvisof Flipbook Maker and refers to the formulation of competency development in 21st century learning in thedomain digital-age literacy which includes 8 aspects. The application of the oriented PjBL model is digital-age literacy proven to be able to increase students' HOTS literacy in science learning material for static electricity class IX SMP.